Chapter Studying Adult Education. A Comparison of Master's Degree Programmes on ALE in Germany and the US - Kleinschmidt, Jessica (Studies on Adult Learning and Education, 2020)
Earning a university degree in adult education continues to be one prominent way of becoming an adult educator. That is because obtaining a comprehensive academic education is considered essential, especially in conjunction with the aim of professionalising adult education. But how do the contents, structure, and aims of study programmes differ internationally, and how does this relate to different concepts of the professional role? This study compares master's programmes in adult education in Germany and the United States. The findings point at characteristic differences in the relation between academics and practice.